PIC32 Microcontrollers and the Digilent Chipkit: Introductory to Advanced Projects - Ibrahim, Dogan (Elsevier Science & Technology, 2015)
PIC32 Microcontrollers and the Digilent chipKIT: Introductory to Advanced Projects will teach you about the architecture of 32-bit processors and the hardware details of the chipKIT development boards, with a focus on the chipKIT MX3 microcontroller development board. Once the basics are covered, the book then moves on to describe the MPLAB and MPIDE packages using the C language for program development. The final part of the book is based on project development, with techniques learned in earlier chapters, using projects as examples. Each projectwill have a practical approach, with in-depth descriptions and program flow-charts with block diagrams, circuit diagrams, a full program listing and a follow up on testing and further development. With this book you will learn: State-of-the-art PIC32 32-bit microcontroller architectureHow to program 32-bit PIC microcontrollers using MPIDE, MPLAB, and C languageCore features of the chipKIT series development boardsHow to develop simple projects using the chipKIT MX3 development board and Pmod interface cardshow to develop advanced projects using the chipKIT MX3 development boards Demonstrates how to use the PIC32 series of microcontrollers in real, practical applications, and make the connection between hardware and software programmingUsage of the PIC32MX320F128H microcontroller, which has many features of the PIC32 device and is included on the chipKIT MX3 development boardUses the highly popular chipKIT development boards, and the PIC32 for real world applications, making this book one of a kind